MSMEs Digitalization: The Future Economic Ecosystem After the Covid-19 Era - Hisar Sirait; Rizqy Aziz Basuki; Sylvia Sari Rosalina; Supriyanto Supriyanto; Erna Sari (Wacana Journal of Social and Humanity Studies, 2022)
In Indonesia, for the last 5 years before the Covid-19 pandemic, MSMEs had a significant role in the economy, where MSMEs contributed an average of 57.8 percent to GDP, 97% absorbed labor, and were able to create 90% of jobs. During the Covid-19 pandemic, the role of MSMEs in the national economy has decreased; MSMEs only contributed 37.3 percent to GDP. Digitizing MSMEs is necessary to survive and develop in the era of the covid 19 pandemic. MSMEs need to be facilitated to go digital and go global. This research examined the future of the economic ecosystem after the covid-19 era in Indonesia. This research used a literature review by analyzing and summarizing selected articles with the same or related topics to MSMEs' digitalization. The results of this research showed that Optimizing MSME digitalization is inseparable from the ability of MSME actors to carry out digital marketing strategies to expand their business marketing network. Second, another aspect that is no less important that MSMEs must pay attention to in utilizing the digital ecosystem is branding, which is defined as introducing products to consumers to enlarge and build a brand from the benefits of these products, and MSMEs must be able to utilize social media such as Facebook, Instagram or Tiktok as promotion and sales channels. Keywords: MSME’s, digitalization, covid-19, economic